Individualized Treatment Strategy for Cutaneous Melanoma: Where Are We Now and Where Are We Going? - Zeng, Huihua; Liu, Fen; Zhou, Hairong; Zeng, Changchun (Frontiers in Oncology, 2021)
In the past several decades, innovative research in cancer biology and immunology has contributed to novel therapeutics, such as targeted therapy and immunotherapy, which have transformed the management of patients with melanoma. Despite the remarkable therapeutic outcomes of targeted treatments targeting MAPK signaling and immunotherapy that suppresses immune checkpoints, some individuals acquire therapeutic resistance and disease recurrence. This review summarizes the current understanding of melanoma genetic variations and discusses individualized melanoma therapy options, particularly for advanced or metastatic melanoma, as well as potential drug resistance mechanisms. A deeper understanding of individualized treatment will assist in improving clinical outcomes for patients with cutaneous melanoma.